Skrining Pendahuluan Toksisitas Beberapa Tumbuhan Benalu terhadap Larva Udang Artemia Salina Leach - DANTI NUR INDIASTUTI; SRI PURWANINGSIH; YUANI SETIAWATI; NOOR CHOLIES (Fakultas Farmasi Universitas Pancasila, 2008)
The brine shrimp lethality test (BSLT) is considered as a useful tool for preliminary assessment of toxicity. It has also been suggested for screening of pharmacological activities of plant extracts. The bioactivity of eight methanol extracts of four parasite plants and two host plants were evaluated using the brine shrimp lethality assay. The results showed that all methanol extracts of the host plants did not have any indication of toxicity The LC50 of methanol extract of Moringa pterygosperma stem was 1085.44±84.32 µg/ml, and of Ficus refusal stem was 1240.86±50.71 µg/ml. But methanol extracts of whole parts of parasite plants showed toxicity to Artemia Salina Leach. The LC50 of methanol extract of Loranthus peretandrus herb parasite was 175.66±29,24 µg/ml while that of Elytranthe evenia leaf parasite was 327.15±38.66 µg/ml; of Elytranthe evenia stem parasite was 320.39±39.57 µg/ml; of Elytranthe evenia flower parasite was 456.79±15.69 µg/ml; of Scurulla atropurpurea herb parasite was 176.44±28.46 µg/ml; and of Viscum articulatum parasite was 53.79±10.83 µg/ml.